A Mild Approach for the Synthesis of Indoles from N-(2-Iodo-aryl)formamides and Phenylacetylene by a Copper(I)- and Palladium-Catalyzed Cascade Process - Ahmed, Atiur; Ghosh, Munmun; Dhara, Shubhendu; Ray, Jayanta K. (Synlett, 2014)
An efficient one-pot copper(I)- and palladium-catalyzed synthesis of indoles from N-(2-iodo-aryl)formamides and phenylacetylene is described. The cascade reaction comprises a Sonogashira cross-coupling, an intramolecular C–N bond formation, and hydrolysis of the intermediate indole-1-carbaldehyde promoted by the same catalyst and base systems.
Keywords: indole; cascade reaction; copper(I) and palladium catalyst; N-(2-iodo-aryl)formamide; hydrolysis